Correlation of the Rates of Solvolysis of Neopentyl Chloroformate—A Recommended Protecting Agent - D’Souza, Malcolm J. (Molecular Diversity Preservation International (MDPI), 2011)
The specific rates of solvolysis of neopentyl chloroformate (1) have been determined in 21 pure and binary solvents at 45.0 °C. In most solvents the values are essentially identical to those for ethyl and n-propyl chloroformates. However, in aqueous-1,1,1,3,3,3-hexafluoro-2-propanol mixtures (HFIP) rich in fluoroalcohol, 1 solvolyses appreciably faster than the other two substrates. Linear free energy relationship (LFER) comparison of the specific rates of solvolysis of 1 with those for phenyl chloroformate and those for n-propyl chloroformate are helpful in the mechanistic considerations, as is also the treatment in terms of the Extended Grunwald-Winstein equation. It is proposed that the faster reaction for 1 in HFIP rich solvents is due to the influence of a 1,2-methyl shift, leading to a tertiary alkyl cation, outweighing the only weak nucleophilic solvation of the cation possible in these low nucleophilicity solvents.